DAMPAK PERUBAHAN PERILAKU KONSUMEN SAAT PANDEMI COVID-19 PADA PENINGKATAN PENJUALAN E-COMMERCE PADA KAB. SUMENEP - Istiyanatul Mahbubah; Sofie Yunida Putri (BAJ: Behavioral Accounting Journal, 2021)
COVID-19 has resulted in various business sectors, especially MSMEs facing far more significant challenges and uncertainties than before, so it is necessary to build greater adaptability through the digitalization process, a challenge for all business sectors to operate efficiently and safely. In addition, one way that can help them maintain efficiency and safe operations during the pandemic is to adopt digitalization or start switching from conventional trading methods to online trading, which is often known as electronic commerce (e-commerce). This spending medium is nothing new. However, due to the limitations and restrictions that existed during the pandemic, consumers tend to experience changes in shopping behaviour, so this will affect the increase in e-commerce business sales. The study aims to identify how the impact of changes in consumer behaviour during the COVID-19 pandemic on increasing sales of e-commerce businesses in Sumenep Regency. This research is quantitative research using SPSS as a test tool. This study concludes that the COVID-19 pandemic has resulted in changes in consumer behaviour that affect the increase in sales of the E-Commerce business in Sumenep Regency, which means that the pandemic has increased income for e-commerce business people when compared to before the COVID-19 pandemic.